Fixed Point Theorems in Non-Archimedean Fuzzy Metric Spaces - Mehra, Seema (International Journal of Applied Mathematical Research, 2012)
The purpose of this paper is to prove common fixed point theorems in Non- Archimedean fuzzy metric space using the concept of semi-compatibility and weak compatibility of pair of self maps. Keywords: Non- Archimedean fuzzy metric space, common fixed point, semi-compatibility, weak-compatibility.